To the Peculiarities of Legal and Non-Legal Regulation of Social Relations in the Field of Sport - Харитонов, Євген Олегович; Харитонов, Є. О.; Харитонов, Евгений Олегович; Kharytonov, Yevhen O.; Kharytonov, Evgen; Харитонова, Олена Іванівна; Харитонова, О. І.; Харитонова, Елена Ивановна; Kharytonova, Оlena I.; Коструба, Анатолій Володимирович; Коструба, А. В.; Коструба, Анатолий Владимирович; et al. (FEADEF, 2020)
Sport is a unique area of social relations, which is officially autonomous and ruled not only and not so much by national law, but to a greater extent – by the rules of sports organizations. Due to the fact that sport has an autonomous character, which, in particular, is characterized by the presence of various regulatory sources that comprehensively affect the relevant social relations, the concept of a unique «sports legal order» is now beginning to take shape. The study aims to analyze social relations in the field of sport and the peculiarities of their regulation. Moreover, the research methodology includes a set of methods of scientific cognition, among which are the methods of analysis, synthesis, induction, deduction, formallogical method, historical method and comparative legal method. Regulation of relations in the field of sports is significantly different from the regulation of other social relations. The presence of such features gives grounds for sports officials to declare the special status of the field of sports and the need to remove it from the general legal order. As a result of the study, the authors of the article came to the conclusion that modern sport has an autonomous status and is a special area of legal and non-legal regulation, which has the characteristics of an independent legal order. At the same time, it is too early to claim the existence of a full-fledged «sports legal order».

Спорт - це унікальна сфера суспільних відносин, яка офіційно є автономною і управляється не тільки і не стільки національним законодавством, скільки більшою мірою - правилами спортивних організацій. У зв’язку з тим, що спорт має автономний характер, що, зокрема, характеризується наявністю різних регуляторних джерел, які всебічно впливають на відповідні суспільні відносини, зараз починає формуватися концепція унікального «спортивного правопорядку». Метою дослідження є аналіз соціальних відносин у галузі спорту та особливостей їх регулювання. Більше того, методологія дослідження включає сукупність методів наукового пізнання, серед яких є методи аналізу, синтезу, індукції, дедукції, формалогічний метод, історичний метод та порівняльно-правовий метод. Регулювання відносин у галузі спорту суттєво відрізняється від регулювання інших суспільних відносин. Наявність таких особливостей дає підставу для спортивних службовців заявити про особливий статус галузі спорту та необхідність вилучення його із загального правового порядку. В результаті дослідження автори статті дійшли висновку, що сучасний спорт має автономний статус і є особливою сферою правового та неправового регулювання, що має характеристики незалежного правового порядку. У той же час ще рано стверджувати про існування повноцінного «спортивного правопорядку».
Kharytonov Е. To the Peculiarities of Legal and Non-Legal Regulation of Social Relations in the Field of Sport / E. Kharytonov, O. Kharytonova, A. Kostruba, M. Tkalych, Yu. Tolmachevska // Retos. – V. 41. – FEADEF, 2020. – Р. 131-137.
Keywords: legal regulation; non-legal regulation; autonomy of sport; sports law; legal order; правове регулювання; неправове регулювання; автономія спорту; спортивне право; правопорядок; правовое регулирование; неправовое регулирование; автономия спорта; спортивное право; правопорядок